COVID-19 aus der Sicht der Gastroenterologie - Schulz, Christian; Mayerle, Julia; Stubbe, Hans Christian; Sirtl, Simon; Lerch, Markus M.; Malfertheiner, Peter (DMW - Deutsche Medizinische Wochenschrift, 2020)
COVID 19, caused by SARS-CoV2, a new variant of coronaviruses, typically presents with respiratory symptoms. However, in a significat number of patients different organs are involved in the disease, often including gastrointestinal symptoms. These could include loss of appetite, vomiting, abdominal pain and diarrhea, with diarrhea being associated with a more severe course of COVID-19. Because viral RNA can be detected in fecal samples, some implications for clinical routine in diagnostic and therapeutic procedures are grown. Until yet, no clear evidence is given regarding fecal-oral transmission of SARS-CoV2.
Keywords: COVID-19; Diarrhö; Gastroenterologie; Endoskopie; Leberbeteiligung